2013
DOI: 10.1165/rcmb.2012-0361oc
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Hyperpolarization in Pulmonary Vascular Remodeling. Mitochondrial Uncoupling Protein Deficiency as Disease Model

Abstract: Alterations of mitochondrial membrane potential (MMP), reactive oxygen species (ROS), and mitochondrial respiration are possible triggers of pulmonary vascular remodeling in pulmonary hypertension (PH). We investigated the role of MMP in PH and hypothesized that deletion of the mitochondrial uncoupling protein 2 (UCP2) increases MMP, thus promoting pulmonary vascular remodeling and PH. MMP was measured by JC-1 in isolated pulmonary arterial smooth muscle cells (PASMCs) of patients with PH and animals with PH i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 42 publications
4
54
0
Order By: Relevance
“…Such a mechanism also seems to contribute to the anti-inflammatory activity of UCPs, 7 an aspect also of relevance to the vascular system; transplantation of UCP2 −/− bone marrow into LDLR −/− mice increased atherosclerosis development, 8 and global UCP2 −/− mice exhibited increased inflammatory activity and enhanced aortic macrophage deposition in response to atherogenic diet. 9 In many cell types, including smooth muscle cells and fibroblasts, ROS-stimulated MAP kinase activation promotes proliferation, and therefore it is unlikely that the antiproliferative effect of UCP2 knockout observed in endo thelial cells in the study by Shimasaki et al 4 is universal; for example pulmonary arterial smooth muscle cells harvested from UCP2 −/− mice exhibited accelerated proliferation 10 and increased apoptosis resistance.…”
Section: Article See P 891mentioning
confidence: 99%
“…Such a mechanism also seems to contribute to the anti-inflammatory activity of UCPs, 7 an aspect also of relevance to the vascular system; transplantation of UCP2 −/− bone marrow into LDLR −/− mice increased atherosclerosis development, 8 and global UCP2 −/− mice exhibited increased inflammatory activity and enhanced aortic macrophage deposition in response to atherogenic diet. 9 In many cell types, including smooth muscle cells and fibroblasts, ROS-stimulated MAP kinase activation promotes proliferation, and therefore it is unlikely that the antiproliferative effect of UCP2 knockout observed in endo thelial cells in the study by Shimasaki et al 4 is universal; for example pulmonary arterial smooth muscle cells harvested from UCP2 −/− mice exhibited accelerated proliferation 10 and increased apoptosis resistance.…”
Section: Article See P 891mentioning
confidence: 99%
“…Genetic ablation of UCP2 in PASMCs demonstrated mitochondrial hyperpolarization, decreased activity of calcium-sensitive mitochondrial enzymes, resistance to apoptosis, and established a proliferative phenotype. The same study showed that in vivo knockout of Ucp2 in mice models activated HIF-1α and NFAT, increased remodeling of the pulmonary vasculature, and developed PH [122,123]. In ECs, the loss of UCP2 resulted in exaggerated PTEN-induced putative kinase 1 (Pink1)-induced mitophagy, decreased mitochondrial biosynthesis, and increased apoptosis, indicating that a UCP2-Pink1 axis might serve as a therapeutic target [124].…”
Section: Novel Targets Of Emerging Metabolic Therapiesmentioning
confidence: 99%
“…Is mt hyperpolarization found under more normal circumstances? It occurs in T-cell activation [95,96], is supposed to be a factor in disease complications upon high blood glucose in diabetes [97], has been observed over longer periods of stress in astrocytes [98], is a characteristic of arterial smooth muscle cells in pulmonary hypertension [99], and is a ‘sensitizing feature’ in apoptotic potential of Caco-2 intestinal cells [100]. Neurons tolerant of transient glutamate excitation show significant mt hyperpolarization in response [101], and it is quite common in many types of cancer cells [102,103].…”
Section: In Vivo: Ret From Complex II Leads To Ros Formation By Complmentioning
confidence: 99%